PENGARUH MEDIA SOSIAL DALAM MEMPREDIKSI PARTISIPASI PERILAKU PEMILIH PEMULA PADA PEMILIHAN UMUM 2024 - Pardana, Deki (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This research uses a qualitative method approach. Data is processed using statistical tools. The sample in this study were 70 people. where the sample preferences in this study were high school students as beginner preferences. the data were processed using statistical tools, SPSS. The results showed that the constant value (a) was 38.228, while social media as a variable (X) had a value of 0.125. This shows that the constant of 38.228 means that the novice voter participation variable is 38.228. While the regression coefficient of the social media variable (X) shows that every 1% increase in the value of social media, the participation of novice voters increases by 0.125. So there is a significant influence between the use of social media on the participation of novice voters. The social media variable (X) has a positive and significant effect on the behavior of novice voters, this can be seen from the significant social media (X1) of 0.02 and the t table value. Means t count of 0.998. So there is an influence of social media on beginner voter participation